Studi eksperimental pengaruh slant angle terhadap peningkatan perpindahan panas pada penukar kalor pipa konsentrik dengan louvered strip insert susunan forward - Indra Setyawan; Agung Tri Wijayanta; Tri Istanto (Jurnal Teknik Mesin Indonesia, 2016)
This study was conducted to investigate the effect of slant angle (α) on heat transfer enhancement in concentric pipe heat exchanger with forward arrangement of louvered strip insert. In this study, louvered strip insert is varied with α = 15o, 20o and 25o. The working fluid in the inner tube was hot water and in the annulus was cold water, with the flows direction were counterflow. Tests were conducted at a Reynolds number (Re) 5300 – 17,500). At 5300 < Re < 17500 the value of Nui in the inner pipe with the addition of louvered strip insert with α = 15o, 20o and 25o increases in the range of 19.04% - 22.86%, 48.09% - 54.83%, and 67.43% - 77.02% compared with Nui of plain tube respectively. At Re 5300 < Re < 17500 The value of friction factor in the inner pipe with the addition of louvered strip insert with α = 15o, 20o and 25o is 1.52, 2.56 and 3.35 times greater than friction factor of plain tube respectively. Heat transfer enhancement ratio with addition of louvered strip insert with α = 15o, 20o and 25o in the range of 1.00 – 1.06, 1.02 – 1.08 and 1.03 – 1.12 respectively.